(untitled) (Asian Journal of Social Science Studies, 2022)
There is a dearth of research content about the integration of Chinese excellent traditional culture and kindergarten curriculum in research studies related to kindergarten curriculum. Most studies begin with the integration of minority cultural characteristics or regional characteristics with the kindergarten curriculum, with only a few studies on kindergarten curriculum with the integrity of Chinese excellent traditional culture as the entry point. We investigated kindergarten teachers‟ awareness of the connotation of Chinese traditional culture, the teaching objectives, content, form, and existing problems of the Chinese cultural characteristics curriculum in Jinshan District, Shanghai, using a questionnaire to obtain authentic and reliable research materials.